STUDY OF MIAO EMBROIDERY: SEMIOTICS OF PATTERNS AND ARTISTIC VALUE - WANG, SHIYANG; KOLOSNICHENKO, O. V. (Art and Design, 2024)
Purpose. This study aims to analyze and interpret the semiotic characteristics of Qiandongnan Miao embroidery patterns based on Morris's semiotic trichotomy. It seeks to explore methods and pathways for the application and transformation of ethnic embroidery patterns in modern cultural and creative design. Methodology. Through field research in the Qiandongnan Miao area, literature collection, and design practice, the study investigates the representative semiotic characteristics of Qiandongnan Miao embroidery patterns in terms of decoration and color. Using Morris's semiotic trichotomy, the research interprets the semiotic relationships among Qiandongnan Miao embroidery patterns from the perspectives of syntactics, pragmatics, and semantics. It explores the innovative application scenarios of traditional cultural symbols in contemporary design contexts. Results. Qiandongnan Miao embroidery patterns exhibit distinct artistic features, regional characteristics, and aesthetic tendencies. By extracting the semiotic elements of decoration and color from the dimensions of syntactics, pragmatics, and semantics, the study explores the multiple transformations and innovative application possibilities of Qiandongnan Miao embroidery pattern design elements. This not only allows modern design products to incorporate ethnic cultural characteristics but also contributes to the inheritance and development of Qiandongnan Miao embroidery patterns. Scientific novelty. This research applies Morris's semiotic trichotomy to the interpretation of Qiandongnan Miao embroidery patterns, providing a new perspective for the cultural connotation and design transformation of traditional embroidery patterns. It explores the pathways and application models for transforming traditional cultural symbols in modern design, seeking ways to integrate traditional culture with contemporary design. Practical significance. The study offers new ideas and references for interpreting and researching Qiandongnan Miao embroidery patterns from a semiotic perspective. It provides references and insights for related design fields.